Appendiceal torsion in Ehlers-Danlos syndrome: A case report of a rare phenomenon in a rare disease. (2020) - Kim, Soobin; Baldwin, Dustin; Duarte, Bernardo
Highlights: Appendiceal torsion, a rare phenomenon, may be seen in Ehlers-Danlos syndrome. Appendiceal torsion is clinically indistinguishable from acute appendicitis. Ehlers-Danlos syndrome contributes to surgical problems due to fragility of tissue. Abstract: Introduction: Appendiceal torsion is a rare phenomenon with only a few reported cases and never in a patient with Ehlers-Danlos syndrome (EDS). We present the first case of appendiceal torsion leading to acute appendicitis in a patient with EDS. Presentation of case: A 36-year-old male with history of musculoskeletal EDS presented with one week of abdominal pain localizing to the right lower quadrant. He was evaluated in the emergency department with a complete set of labs and CT abdomen/pelvis. The CT scan showed acute appendicitis, but did not mention any appendiceal torsion. He was taken to the operating room for a standard laparoscopic appendectomy. Intraoperatively, there was inflammation at the tip of the appendix with a 270-degree torsion of the mid-appendix and mesoappendix. After untwisting, the appendix was safely removed from the base of the cecum. Patient recovered well postoperatively and no masses or tumors were identified on final pathology. Discussion: Primary appendiceal torsion occurs without an identifiable cause and secondary torsion occurs due to pathology such as carcinoid tumor or other masses. Patients with EDS may be more prone to either torsion as they have hyperelastic skin, joints and ligaments. EDS patients require special workup prior to any operation including cardiopulmonary evaluation and may have unique postoperative complications. Conclusion: The ligamentous hypermobility of EDS may have predisposed our patient to appendiceal torsion and acute appendicitis. This is a rare phenomenon and may be underdiagnosed in EDS patients. Practitioners should be aware of this manifestation of EDS.